KONSEP DIRI POSITIF PADA ANAK PEDAGANG ASONGAN DI SIMPANG PADANG HARAPAN KOTA BENGKULU - Hermi Pasmawati; Okta Viani; Rina Qurrota Ayun; D Dellvianti (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
This study aims to find out the positive self-concept in hawker children while on the streets with various kinds of jobs such as selling tissues, selling newspapers, selling crackers and so on. This type of research is qualitative with a descriptive approach. The informant selection technique uses purposive sampling technique with the number of informants 5 people, who are male, and aged 12-16 years. Data collection techniques using observations and interviews with data analysis used Milers and Huberman models. The research findings found that there was a positive self-concept in hawker children. There are aspects of self-concept that are positf in terms of the work done, future expectations about him towards the ideals he has, and his current state of self in assessing what he does.